Kriminalisasi Trading in Influence dalam Tindak Pidana Korupsi - Syahird, Ahmad; Marlin, Marlin (Al-Mizan (e-Journal), 2023)
This research aims to find out the concept of trading in influence in the United Nations Convention Against Corruption (UNCAC) and to find out the urgency of criminalizing trading in influence in Indonesian legislation. This type of research is normative research with a statute approach and a conceptual approach. The results of this study show that the concept of trading in influence in UNCAC has differences with the crime of corruption in national legislation, such as in terms of perpetrators and arrangements. The absence of trading in influence regulation in the legislation is the urgency of the need for trading in influence in the future law (ius constituendum). The concept of trading in influence in UNCAC is similar to the offense of active-passive bribery by public officials, which is already regulated in the corruption law. However, it still differs in the recipient of the bribe, the setting, and the person involved. Meanwhile, the urgency of regulating trading in influence in national legislation is because corruption has become a problem for the international community and there is also a legal vacuum.